Analysis Of Hybrid Relay Selection In SDR-Based Cooperative Systems - Ummul Khair; Ihsan Lumasa R; Vera Veronica; Lifwarda Lifwarda; Silfia Rifka (Brilliance: Research of Artificial Intelligence, 2025)
The cooperative communication system, involving multiple nodes that assist each other in data transmission, has been studied. In this system, the source sends information not only directly to the destination but also through an intermediate relay node. The relay receives the signal, which is then forwarded to the destination, resulting in the reception of two copies of the signal. Combining these signals results in enhanced strength and reliability. This configuration addresses signal fading issues commonly encountered in wireless communication due to reflection, scattering, and interference. The Hybrid Relay Protocol (HRP), combining Decode-and-Forward (DF) and Amplify-and-Forward (AF) methods, was implemented to improve relay efficiency and adaptability. The relay’s protocol choice depends on instantaneous Signal-to-Noise Ratio (SNR); if the SNR exceeds a threshold, DF is applied by decoding and forwarding a clean signal, otherwise, AF is used by amplifying and forwarding the received signal without decoding. Relay selection is optimized based on channel gains using a harmonic mean metric. MATLAB simulations demonstrated that the HRS system, with relay distances ranging from 4 to 12 meters, achieves significantly improved Bit Error Rate (BER) performance, for instance, obtaining BER as low as 0.00012 at 4 meters and ?23.5 dBm transmit power. Additionally, maximal ratio combining was employed at the destination, enhancing signal reliability. The results confirm the effectiveness of the HRS system for real-time applications on Software-Defined Radio (SDR) platforms, with potential for improving wireless network robustness under diverse channel conditions.